Давне чинбарство на території України - Войнаровський, В.М. (Археологія, 2003)
У статті розглянуто результати досліджень чинбарського спеціалізованого комплексу черняхівської культури ІІІ—IV ст. біля с. Добринівці. Статья посвящена одному из наиболее распространенных в древности и одновременно недостаточно уловимому археологически типу производства — кожевничеству. Основу работы составляют артефакты производства кожи, выделенные автором на материале Кожевнических специализированных комплексов Черняховской культуры Добрыновцы-1 на Буковине и «Перун» в предместье позднесредневекового Львова. Приведены результаты палеоэкономического анализа исследуемых комплексов, реконструирована технологическая цепочка древнего кожепроизводства, описан многочисленный ряд археологических артефактов кожевничества (стационарных и движимых), даны рекомендации по усовершенствованию методики поиска и интерпретации объектов и центров древнего кожевничества. The article deals with one of the most widespread at the ancient period and at the same time not enough perceptible by archaeological sources type of manufacturing - the tanning industry. The leather artifacts singled out by the author from among the material of specified tanning assemblages of Chemiakhivs’ka culture such as Dobrynovtsy-I in the region of Bukovina, and «Perun» in the suburb of late medieval Lvov are in the center of attention in this paper. The author presents results of the paleoeconomical analysis of the assemblages under study, makes reconstruction of the technological chain of the ancient tanning industry, shows numerous archaeological leather artifacts (stationary and portable), and adduces recommendations for improvement of methodology of searching and interpretation of objects and sites of the ancient tanning industry.